PERLAKUAN AKUNTANSI ASET TETAP TERHADAP LAPORAN KEUANGAN DESA DENGAN METODE AKRUAL PADA KANTOR DESA PANJARATAN KECAMATAN PELAIHARI KABUPATEN TANAH LAUT PERIODE 2017-2019 - Yuli Fitriyani; Mufrida Zein; Jevry Jevry (Jurnal Riset Akuntansi Politala, 2023)
Accounting plays an important role in financial reports and one of them is fixed assets. The recording and management of fixed assets is disclosed in the government's financial reports, especially in Panjaratan Village. This research was conducted to determine whether there is conformity in the accounting treatment of the fixed assets of the Panjaratan Village office with the Government Accounting Standards (SAP) based on Government Regulation (PP) No. 71 of 2010 and find out the suitability between village fixed asset management and Minister of Home Affairs Regulation No. 01 of 2016. The method the researcher uses is a qualitative descriptive method by comparing the main accrual-based theories with the conditions that occur at the Panjaratan Village office as seen from the report financial period 2017-2019. The results obtained from this study are the recording of fixed asset transactions, the application of government accounting standards and the disclosure of fixed assets at the Panjaratan Village office in general are in accordance with Government Accounting Standards as well as the management of Panjaratan village assets which are also in accordance with Permendaggri No 01 of 2016.